A case of corticosteroid‐refractory adult‐onset Still's disease successfully controlled with tocilizumab despite transient neutropenia and thrombocytopenia. Issue 3 (3rd May 2021) - Iwata, Jun‐ichi; Yamamura, Hitomi; Takano, Aiko; Horiuchi, Yoshihito
Abstract: We report a case of a 50‐year‐old woman with adult‐onset Still's disease (AOSD). Even after receiving steroid pulse therapy and high‐dose oral corticosteroid medication, the patient's serum ferritin level increased, while the number of neutrophils and platelets decreased. However, fever, erythema, sore throat, and arthralgia ceased. Therefore, we administered intravenous tocilizumab (TCZ). However, neutropenia, thrombocytopenia, and exacerbation of hyperferritinemia occurred after the first TCZ infusion. After the second TCZ infusion, the values returned to normal, and we discontinued prednisolone successfully without any flare‐ups of AOSD. We reviewed case reports describing adverse events after TCZ administration in AOSD patients. Abstract : We report the case of a 50‐year‐old woman with corticosteroid‐refractory adult‐onset Still's disease (AOSD). We administered intravenous tocilizumab (TCZ), but neutropenia, thrombocytopenia, and exacerbation of hyperferritinemia occurred after the first TCZ infusion. After the second TCZ infusion, the values returned to normal, and we discontinued prednisolone successfully without any flare‐ups of AOSD.